ANTIOXIDANT ACTIVITIES, PHENOLS AND FLAVONOID CONTENTS OF CURCUMA LONGA L. AND CURCUMA CAESIA ROXB. FOUND IN MANIPUR - KANANBALA SARANGTHEM; MANGVUNG JAMKHONENG HAOKIP (The Bioscan, 2012)
In the present study, a systematic record of the relative antioxidant activity in two selected medicinal plant species extracts is carried out. Findings indicated higher levels of total phenols (220±0.060 mg/g, 60±0.03 mg/g) and flavonoid (132±0.03, 30±0.06 mg/g dry weight of the root tissue) contents in the rhizome extracts of C. longa compared to C. caesia. The percentage of inhibition increases from 10μg/mL till 60 μg/mL and beyond which there is no increased in inhibition. The extend of inhibition by quercetin which is used as standard compound is 84%, C. longa 81.6% and C. caesia 76.24% respectively.